2021
DOI: 10.1002/epi4.12464
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 lockdown on patients and families with Dravet syndrome

Abstract: We explored the impact of coronavirus virus 2019 (COVID‐19) pandemic on patients with Dravet syndrome (DS) and their family. With European patient advocacy groups (PAGs), we developed an online survey in 10 languages to question health status, behavior, personal protection, and health services before and after lockdown. Approximately 538 European PAG members received electronic invitations. Survey ran from April 14, to May 17, 2020, with 219 answers; median age 9 year 10 months. Protection against infection wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Individuals with behavioural problems in both periods exhibited more severe disorders during lockdown, including more pronounced aggressivity, self-aggressivity, depressiveness, stereotypies, and restricted interests than in the pre-lockdown period. These results echoed past studies that showed higher behavioural problems during lockdown in developmental and ID [ 10 , 33 , 34 ], Down Syndrome [ 12 ], Prader-Willi Syndrome [ 22 ], Fragile X [ 21 ] and Dravet Syndrome [ 35 ]. Depression in people with ID often presents atypically, with agitation and irritability rather than a sad mood [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…Individuals with behavioural problems in both periods exhibited more severe disorders during lockdown, including more pronounced aggressivity, self-aggressivity, depressiveness, stereotypies, and restricted interests than in the pre-lockdown period. These results echoed past studies that showed higher behavioural problems during lockdown in developmental and ID [ 10 , 33 , 34 ], Down Syndrome [ 12 ], Prader-Willi Syndrome [ 22 ], Fragile X [ 21 ] and Dravet Syndrome [ 35 ]. Depression in people with ID often presents atypically, with agitation and irritability rather than a sad mood [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…The implications of disruption to these medications may have significant consequences. Cessation of anti-seizure medication, for example, may contribute to the increased seizure frequency during the pandemic ( Brambilla et al, 2021 ; Trivisano et al, 2020 ) and drug withdrawal is a risk factor for status epilepticus, which may be fatal ( Nair et al ., 2011 ). It is not only those with IDD who experienced challenges in accessing healthcare, however, as the present study found that family members supporting persons with IDD also avoided healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…arthritis or diabetes, which is referable to the loss of resources due to the pandemic [ 28 , 29 ]. In addition to that, patients with physical and mental disabilities, like those suffering from developmental and epileptic encephalopathies, and their caregivers might be even more affected by the pandemic [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%